2012
DOI: 10.1016/j.jamcollsurg.2012.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Introducing Hematoma Ultrasound-Guided Lumpectomy in a Surgical Practice

Abstract: BACKGROUND Preoperative needle localization (NL) is the gold standard for lumpectomy of nonpalpable breast cancer. Hematoma ultrasound-guided (HUG) lumpectomy can offer several advantages. The purpose of this study was to compare the use of HUG with NL lumpectomy in a single surgical practice. STUDY DESIGN Patients with nonpalpable lesions who underwent NL or HUG lumpectomy from January 2007 to December 2009 by a single surgeon were identified from a breast surgery database. Ease of scheduling, volume excise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The authors reported, however, that a significantly greater number of intraoperative re-excisions were performed during primary surgery with HUG than with WGL (P = 0.04), resulting in additional tissue being sent to pathology; 90 nevertheless, no significant difference in overall tissue-volume excised (P = 0.57) was observed, and the impact of additional intraoperative re-excisions on cosmetic outcome was not addressed. 90 No other difference was reported between the two techniques. This modification of IOUS demonstrates potential benefits of ultrasonography, but requires assessment within prospective, randomized trials to exclude the inherent limitations of the performed retrospective studies.…”
Section: Clinical Evidencementioning
confidence: 93%
See 1 more Smart Citation
“…The authors reported, however, that a significantly greater number of intraoperative re-excisions were performed during primary surgery with HUG than with WGL (P = 0.04), resulting in additional tissue being sent to pathology; 90 nevertheless, no significant difference in overall tissue-volume excised (P = 0.57) was observed, and the impact of additional intraoperative re-excisions on cosmetic outcome was not addressed. 90 No other difference was reported between the two techniques. This modification of IOUS demonstrates potential benefits of ultrasonography, but requires assessment within prospective, randomized trials to exclude the inherent limitations of the performed retrospective studies.…”
Section: Clinical Evidencementioning
confidence: 93%
“…The largest study by Arentz et al 89 90 identified a reduction in time-to-theatre in patients undergoing HUG, probably because this technique avoids the need for an additional radiology appointment and HUG was associated with lower costs ($250 cheaper) than WGL. The authors reported, however, that a significantly greater number of intraoperative re-excisions were performed during primary surgery with HUG than with WGL (P = 0.04), resulting in additional tissue being sent to pathology; 90 nevertheless, no significant difference in overall tissue-volume excised (P = 0.57) was observed, and the impact of additional intraoperative re-excisions on cosmetic outcome was not addressed.…”
Section: Clinical Evidencementioning
confidence: 99%
“…Many methods can be used for the localization of lesions. For example, WGL and SGL techniques, carbon black powder, ultrasound‐guided localization, the ROLL technique, the use of radioactive seeds, dye injection, the use of hydrogel‐encapsulated clips, localization with SAVI SCOUT and indocyanine green fluorescence‐guided occult lesion localization (IFOLL) …”
Section: Discussionmentioning
confidence: 99%
“…If the lesion has been excised via vacuum‐assisted biopsy then the post‐biopsy hematoma may be used to guide excision. Limitations of the technique include the learning curve of US operators' skills and the timing of surgery within 4 weeks to avoid resorption of hematoma.This technique has been demonstrated to achieve negative margins of resection equivalent to wire‐guided localization with a significantly smaller resection volume .…”
Section: Historical Techniquesmentioning
confidence: 99%